Deep water circulation in the Arabian Sea during the last glacial cycle: Implications for paleo-redox condition, carbon sink and atmospheric CO2 variability. (1st April 2021) - Lathika, N.; Rahaman, Waliur; Tarique, Mohd; Gandhi, Naveen; Kumar, Avinash; Thamban, Meloth
Abstract: Global overturning circulation plays a vital role in atmospheric CO2 and climate variability during glacial-interglacial (G-I) cycles; however, the exact mechanism remains elusive due to inadequate knowledge on past deep water circulation in the global ocean. Since no deep water is formed in the northern Indian Ocean, it ventilates from the south and acts only as a host for deep water circulation. Absence of any active deep water formation makes the northern Indian Ocean an ideal location to assess the extent of southern source waters and its role on past CO2 variability during the G-I climate cycles. This study provides the first record of deep water circulation in the Arabian Sea, the northwestern Indian Ocean, during the past 136 ka based on authigenic Nd isotope record (εNd ). The Arabian Sea εNd record shows large variability ranging from −8.8 to −6.5 with more radiogenic values during the glacial stages (MIS 2 & 6) and less radiogenic values during the interglacial stages (MIS 1 & 5) indicating changes in water mass sources. The observation of more radiogenic εNd values similar to the glacial Antarctic Bottom Water (AABW) indicates enhanced flow of AABW (95–100%) and substantial reduction and/or almost complete retreat of North Atlantic Deep Water (NADW, 0–5%) during the glacials, whereas less radiogenic values indicate enhanced flow of NADW (∼20–40%) during the interglacials. The Arabian Sea εNd record followed exactly similar pattern to that of the equatorial Indian Ocean (EIO). However, amplitude of their variations differed significantly during the interglacials (MIS 1 & 5); the Arabian Sea εNd values were more radiogenic than the EIO. This suggests that during the interglacials, the Arabian Sea received more fraction of AABW through the western pathway, whereas the EIO received more fraction of NADW through the central pathway. This highlights differences in deep water exports from the Southern Ocean to the Arabian Sea and the EIO during the interglacials whereas export of similar water masses and its uniform distribution up to the northern Indian Ocean during the glacials. Our findings of significant G-I changes in AABW and NADW exports to the Indian Ocean and intra-basinal differences in their distribution have important implications for regional biogeochemical processes, paleo-redox conditions in the water column, carbon sink (organic and inorganic) and atmospheric CO2 variability during the G-I climate transitions. Highlights: First record of deep water circulation (DWC) in the Arabian Sea for the past 135 ka. Nd isotope record indicates significant glacial-inter glacial (G-I) changes in DWC. Variable export of NADW & AABW via different pathways during interglacial stages. Enhanced export and uniform distribution of AABW in Indian Ocean during glacials. G-I changes in AABW-NADW export influenced carbon sink and redox conditions.